Effect of multidisciplinary health education based on lifestyle medicine on menopausal syndrome and lifestyle behaviors of menopausal women: A clinical controlled study - Yangmei Li; Yangmei Li; Yangmei Li; Yangmei Li; Haiyang He; Haiyang He; Haiyang He; Haiyang He; Jiaxi Wang; Yifan Chen; Chunyuan Wang; Xinyue Li; et al. (Frontiers Media S.A., 2023)
BackgroundMenopausal women may experience menopausal syndrome and long-term effects caused by low estrogen levels, such as senile dementia and osteoporosis in the elderly. Most menopausal women may have misconceptions about menopause and low use of pharmacological interventions. These misconceptions may damage the quality of life and miss the critical period for preventing senile diseases. Thus, enhancing the awareness of menopausal women regarding psychosocial and physical changes through health education programs was a way to improve positive attitudes toward menopause and make further treatment options.ObjectivesThis study aimed to evaluate the effect of multidisciplinary health education based on lifestyle medicine on menopausal syndrome and lifestyle behaviors of menopausal women.MethodsThe study was conducted in several hospitals in Chongqing, China. The two groups were from different hospitals with similar medical levels in order to reduce information contamination. It was designed as a clinical controlled trial in which the intervention group (n = 100) and control group (n = 87) were matched for age, age at menarche, menopausal symptoms and drug use status at enrollment. Women in the intervention group received multidisciplinary health education based on lifestyle medicine for 2 months while those in the control group received routine outpatient health guidance. Menopausal syndrome, physical activity and dietary status of participants were assessed before and after the intervention. Paired t-tests and Independent-sample t-tests were adopted for comparison within and between groups, respectively, in the normal variables. Wilcoxon signed-rank tests and Mann-Whitney U tests were adopted for comparison within and between group, respectively, in the abnormal variables. Categorical variables were tested using Pearson's χ2. P-value < 0.05 was statistically significant in statistical tests.ResultsPost intervention testing indicated that menopausal syndrome of participants was significantly improved in the intervention group compared to the control group (P < 0.001). Between-group comparison showed a significant improvement of weekly energy expenditure of total physical activity (P = 0.001) and participation in exercise (P < 0.001) in the intervention group compared to the control group after the intervention. The dietary status of participants was significantly improved in the intervention group compared to the control group (P < 0.001). In the intervention group, the menopausal syndrome of participants improved more in the hormone drug group than in the non-hormone group (P = 0.007), as did the control group (P = 0.02). In the hormone drug group, the physical activity (P = 0.003) and dietary status (P = 0.001) mproved more in the intervention group than in the control group.ConclusionsThe multidisciplinary health education based on lifestyle medicine was effective in improving the menopausal syndrome and healthy lifestyle behaviors of menopausal women. Studies with extended observation period and larger sample size are in need to evaluate the long-term scale-up effects of the multidisciplinary health education.